Modeling Biblical Language : selected papers from the McMaster Divinity College Linguistics Circle - Porter, Stanley E., 1956-; Fewster, Gregory P.; Land, Christopher D. (Linguistic Biblical Studies, 2016)
Modeling Biblical Language presents articles with some of the latest scholarship applying linguistic theory to the study of the Christian Bible. The contributors are all associated with the McMaster Divinity College Linguistic Circle, a collegial forum for presenting working papers in modern linguistics (especially Systemic Functional Linguistics) and biblical studies. The papers address a range of topics in linguistic theory and the Hebrew and Greek languages. Topics include linguistic model building, temporality and verbal aspect, Greek lexical semantics and Hebrew-Greek translation, appraisal and evaluation theory, metaphor theory, corpus linguistics, discourse analysis, and Greek clausal structure. These various areas of linguistic exploration contribute generally to the interpretation and analysis of the Old and New Testaments, as well as to linguistic theory proper.